DEVELOPING ENGLISH FOR TOURISM MATERIALS TROUGH STAKEHOLDERS’ NEEDS ANALYSIS - Indah Puspitasari (English Review: Journal of English Education, 2018)
Banyumas currently grows well in various aspects especially in tourism. Tourism plays an important role in this regency because it becomes one of the mainstays of Banyumas revenue sector. A phenomenon occurs today is the number of hotels in Banyumas arises every year. It is very important to prepare human resources; especially those who have good skills in tourism and English. This paper aims at explaining the stakeholders’ overview of skills needed, topic needed, and difficulties encountered. The stakeholders here are tour agencies, hotels, and Youth, Sports, Culture and Tourism Office of Banyumas Regency. This is a qualitative research method which has several research steps. First, library study is a method of collecting data and it is also used to compile research instruments. The second step is to share the questionnaires to the sampling and the last is analysing the results. The results of this study showed that; 1) the required skills are speaking (100%), listening (75%), writing (25%), and reading (25%), 2) 80% of the topics offered in the questionnaire are required by all stakeholders. The topics are about hotels and tourism materials, and 3) difficulties encountered in active cooperating with tourism industry, less practice in explaining tourism city map, and listening different accents such as English speakers from China, Japan, and India. In conclusion, these findings regarding the skills and topics needed can be used to develop English for Tourism materials.Keywords: English for tourism; English for specific purposes; needs analysis; developing materials; tourism; Banyumas.